Growth and macronutrient accumulation in tomato cultivated in an organic system - De Almeida, Luciana G.; Cardoso, Antonio Ismael Inácio [UNESP]; Candian, Joara S. [UNESP]; Filho, Helio Grassi [UNESP]; Sartori, Maria Márcia P. [UNESP] (FapUNIFESP (SciELO), 2023)
The aim of this study was to characterize the growth and nutrient absorption of ‘Debora Victory’ tomato grown in organic system. The treatments consisted of nine sampling dates, at 2, 32, 46, 60, 77, 91, 109, 122 and 137 days after transplantation (DAT). In the last sampling, plants reached an estimated accumulation of dry and fresh weight in plant shoots of 550 and 9,528 g/plant, respectively. At the end of the cycle, the distribution of dry matter was 73% in the fruits, 16% in the leaves and 11% in the stem. The yield of total fresh fruits was estimated at 154.7 t/ha. The decreasing order of nutrient accumulation in plant shoots was K>N>Ca>P>S>Mg, with estimated values of 22.6; 10.4; 5.0; 2.3; 2.1 and 1.6 g/plant, respectively, corresponding to 431; 198; 95; 44; 40 and 30 kg/ha of K, N, Ca, P, S and Mg, respectively. The decreasing order of nutrient accumulation in the fruits was K>N>P>S>Mg>Ca, with estimated values of 16.6; 8.4; 1.7; 0.8; 0.7 and 0.2 g/plant, respectively, which corresponded to an estimated total extraction of 315; 153; 32; 16; 14 and 3 kg/ha of K, N, P, S, Mg and Ca, respectively. In the last sampling, the greatest accumulation of N, P and K occurred in the fruits and Ca, S and Mg in the vegetative organs (stem + leaves).
Keywords: Dry matter; Nutrient accumulation; Organic agriculture; Solanum lycopersicum